Advances on the synthesis of porous TiO2 coatings by anodic spark oxidation: photocatalytic reduction of Cr(VI) - Traid, Hernán Darío (2017)
Porous TiO2 coatings were obtained by anodic oxidation in spark discharge conditions, varying the range of current density (200-3000 A m−2) and the electrolyte concentration (H2SO4; 1 and 4 M). The samples were characterized by SEM, XRD and DRS. The photocatalytic activity was evaluated using the Cr(VI)/EDTA reductive system to find the optimal conditions for a high photocatalytic activity. A higher electrolyte concentration increased the pore diameter, the porous fraction and the coating thickness and, consequently, the photocatalytic activity; a higher current density improved the performance of coatings. A relationship between the anatase fraction and the photocatalytic activity of the samples was demonstrated, with a maximum activity close to 0.65 anatase fraction. The thermal treatment of the anodic coatings improved also the photocatalytic activity, without changes on neither the morphology nor the anatase fraction. The maximum Cr(VI) transformation achieved by the most active coating was 89.1% while a coating prepared with Evonik P25 achieved only 69.9%. The obtained TiO2 anodic coatings present great potential for application in heterogeneous photocatalysis processes in water and wastewater treatment as supported photocatalysts.